How Honey Bee Vitellogenin Holds Lipid Cargo: A Role for the C-Terminal - Leipart, Vilde; Halskau, Øyvind; Amdam, Gro V. (Frontiers in Molecular Biosciences, 2022)
Vitellogenin (Vg) is a phylogenetically broad glycolipophosphoprotein. A major function of this protein is holding lipid cargo for storage and transportation. Vg has been extensively studied in honey bees (Apis mellifera) due to additional functions in social traits. Using AlphaFold and EM contour mapping, we recently described the protein structure of honey bee Vg. The full-length protein structure reveals a large hydrophobic lipid binding site and a well-defined fold at the C-terminal region. Now, we outline a shielding mechanism that allows the C-terminal region of Vg to cover a large hydrophobic area exposed in the all-atom model. We propose that this C-terminal movement influences lipid molecules' uptake, transport, and delivery. The mechanism requires elasticity in the Vg lipid core as described for homologous proteins in the large lipid transfer protein (LLTP) superfamily to which Vg belongs. Honey bee Vg has, additionally, several structural arrangements that we interpret as beneficial for the functional flexibility of the C-terminal region. The mechanism proposed here may be relevant for the Vg molecules of many species.